Rapid Feedback : The Role of Community Scorecards in Improving Service Delivery - Post, David; Agarwal, Sanjay; Venugopal, Varsha (World Bank, Washington, DC, 2014)
Social accountability tools are increasingly recognized as a means of improving service delivery and governance in World Bank-supported projects. Social accountability is an approach that relies on civic engagement in that citizens participate directly or indirectly in demanding accountability from service providers and public officials. Community scorecards (CSCs), the focus of this note, are citizen-driven accountability measures that enhance citizens' civic involvement and voices and complement conventional supply-side mechanisms of accountability, such as political checks and balances, accounting and auditing systems, administrative rules, and legal procedures. As a community-based social accountability tool, the CSC can be used to gather feedback from service users and improve communication between communities and service providers. By using focus groups and facilitated interface meetings, the CSC process provides service users with the opportunity to give systematic and constructive feedback to service providers about their performance. It also helps service providers learn directly from service users about what aspects of their services and programs are working well and what aspects are not. This note aims to outline a methodology in order to help task team's work with clients to implement and scale-up CSC initiatives. To this end, examples from Bank-supported projects in which the use of CSCs has resulted in improved service delivery are showcased.